'You Want Me to Sing?' Holocaust Testimonies in the Intersubjective Field. Issue 2 (4th May 2018) - Skorczewski, Dawn
ABSTRACT: Studies of Holocaust testimonies often depict survivors as traumatized victims who require the therapeutic assistance of interviewers to tell their stories. This paper focuses on six testimonies from the Visual History Archive to argue instead that each Holocaust testimony is the conjoint product of an intersubjective field that shapes its content. By studying moments when survivors struggle to describe experiences of intense physical and emotional suffering, the author illustrates how their testimonies emerge through an active exchange involving the interviewer, the survivor, and the archiving institutional context. Together they generate an intersubjective field that structures the ensuing narrative and the creation of historical memory.